2014
DOI: 10.1016/j.yexmp.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Divergent and dynamic activity of endogenous retroviruses in burn patients and their inflammatory potential

Abstract: Genes constitute ~3% of the human genome, whereas human endogenous retroviruses (HERVs) represent ~8%. We examined post-burn HERV expression in patients’ blood cells, and the inflammatory potentials of the burn-associated HERVs were evaluated. Buffy coat cells, collected at various time points from 11 patients, were screened for the expression of eight HERV families, and we identified their divergent expression profiles depending on patient, HERV, and time point. The population of expressed HERV sequences was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Some authors already focused on HERV detection in blood of burn patients using pan-family RT-PCRs (Y.-J. Lee et al 2013; K.-H. Lee et al 2014). However, very few data are available in human diseases for specific loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors already focused on HERV detection in blood of burn patients using pan-family RT-PCRs (Y.-J. Lee et al 2013; K.-H. Lee et al 2014). However, very few data are available in human diseases for specific loci.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, HERVs expression has been detected in the plasma and whole blood samples of burn patients (Y.-J. Lee et al 2013; K.-H. Lee et al 2014) although the studies focused on whole HERVs families, not on specific loci. Studying HERV transcriptome modulation after severe inflammatory injuries could help to better understand pathological states of patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that certain TREome genes, such as the envelope genes of MLV-ERVs and MMTV-ERV SAg genes, play functional roles in biological processes (Bentvelzen, 1992; Huber et al, 1994; Kotzin et al, 1993). In addition, TREome (human endogenous retroviruses) gene isoforms isolated from a human burn patient's genomic DNA demonstrated differential potentials for regulating inflammatory mediators, such as IL-6 and IL-1β (Lee et al, 2014). Despite the previous studies which reported a range of functionality of TREome genes in both mice and humans, unfortunately, they are often called non-coding long RNAs in current literature (Geisler and Coller, 2013; Gibb et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These retrovirus-like sequences consist of approximately 200,000 human endogenous retroviruses (HERVs) and 240,000 mammalian apparent long terminal repeat retrotransposons (MaLR). The expression of HERVs has been observed in both inflammation [14,15] and immunosuppression [13,16], and the insertional polymorphism of HERV LTRs at the HLA locus has been associated with several auto-immune diseases [17]. In addition, several lines of evidence support the role of HERVs as contributors to the immune response [18].…”
Section: Introductionmentioning
confidence: 99%